Sustainable production of tilapias (Oreochromis niloticus): essential oils associated with prebiotic and probiotic as an alternative to conventional antibiotics - Albuquerque, Ana Luísa Holanda de (2026)
As a consequence of the global expansion of aquaculture, bacterial diseases with major economic impact have emerged. This increase is largely attributed to higher stocking densities, suboptimal sanitary practices, and the introduction of non-native species, which create favorable conditions for pathogen proliferation and transmission. Conventional treatment relies on antibiotic therapy, which, despite its widespread use, contributes to the development of antimicrobial resistance and causes negative environmental impacts. Sustainable aquaculture must therefore not only maximize productivity but also minimize waste accumulation and other adverse effects on the natural and social environment. In this context, aiming to develop a novel product for sustainable fish production from water to plate, this study investigated an alternative to commercial antibiotics in terms of antimicrobial efficacy and growth-promoting potential. To this end, essential oils (EOs) from Thymus vulgaris, Thymus zygis, and Lippia sidoides, associated with the prebiotic oat β-glucan and the probiotic Bacillus subtilis, were evaluated against Streptococcus agalactiae, the pathogen responsible for the majority of economic losses in Nile Tilapia production, one of the most important species in global aquaculture. The preclinical in vitro study demonstrated the efficacy of the proposed formulation against S. agalactiae, showing a bactericidal effect at a concentration of 0.5 mg/mL. Furthermore, the in vivo trial confirmed that the formulation reduced mortality caused by S. agalactiae infection when used prophylactically. Fish receiving the essential oil blend, either alone or in association with oat β-glucan and B. subtilis, for 55 days prior to the challenge exhibited a 25% reduction in mortality compared with the positive control group. In addition, fish fed the complete formulation showed greater weight gain, higher daily feed intake, increased specific growth rate, and lower feed conversion ratio. Under the conditions of this study, the association of essential oils from T. vulgaris, T. zygis, and L. sidoides with oat β-glucan and B. subtilis demonstrated efficacy both as a growth promoter and as an antimicrobial agent against S. agalactiae in Nile Tilapia. Overall, the combined use of essential oils, prebiotics, and probiotics represents a promising strategy to reduce antibiotic use in fish farming.